Colonization of Vitis vinifera L. by the Endophyte Trichoderma sp. Strain T154: Biocontrol Activity Against Phaeoacremonium minimum - Carro-Huerga, Guzmán; Compant, Stéphane; Gorfer, Markus; Cardoza, Rosa E.; Schmoll, Monika; Gutiérrez, Santiago; Casquero, Pedro A. (Frontiers in Plant Science, 2020)
Trichoderma strains used in biological control products usually exhibit high efficiency in the control of plant diseases. However, their behavior under field conditions is difficult to predict. In addition, the potential of indigenous strains has been poorly assayed as well as their possible behavior as endophytes. Hence, niche colonization is a key feature for an effective protection. In this study, we aimed to: (i) explore the possibility of using a new Trichoderma strain isolated from vine to control pathogens, (ii) study the in planta interaction with the pathogen Phaeoacremonium minimum W. Gams, Crous, M.J. Wingf. & L. Mugnai (formerly Phaeoacremonium aleophilum), a pioneer fungus involved in Grapevine Trunk Diseases (GTDs) such as esca. For this purpose, fluorescently tagged Trichoderma sp. T154 and a P. minimum strain were used for scanning electron microscopy and confocal scanning laser microscopy analyses. Data showed that the Trichoderma strain is able to colonize plants up to 12 weeks post inoculation and is located in xylem, fibers, as well as in parenchymatic tissues inside the wood. The beneficial fungus reduced colonization of the esca-related pathogen colonizing the same niches. The main observed mechanism involved in biocontrol of Trichoderma against the esca pathogen was spore adhesion, niche exclusion and only few typical hypha coiling was found between Trichoderma and the pathogen. These results suggest that the Trichoderma strain has potential for reducing the colonization of Phaeoacremonium minimum and thus, an inoculation of this biological control agent can protect the plant by limiting the development of GTD, and the strain can behave as an endophyte.